Thermal modification of activated carbon surface chemistry improves its capacity as redox mediator for azo dye reduction - Pereira, Luciana (2010)
The surface chemistry of a commercial AC (AC0) was selectively modified, without changing significantly its textural properties, by chemical oxidation with HNO3 (ACHNO3 ) and O2 (ACO2 ), and thermal treatments under H2 (ACH2) or N2 (ACN2 ) flow. The effect of modified AC on anaerobic chemical dye reduction was assayed with sulphide at different pH values 5, 7 and 9. Four dyes were tested: Acid Orange 7, Reactive Red 2, Mordant Yellow 10 and Direct Blue 71. Batch experiments with low amounts of AC (0.1 g L−1) demonstrated an increase of the first-order reduction rate constants, up to 9-fold, as compared with assays without AC. Optimum rates were obtained at pH 5 except for MY10, higher at pH 7. In general, rates increased with increasing the pH of point zero charge (pHpzc), following the trend ACHNO3 < ACO2 < AC0 < ACN2 < ACH2 . The highest reduction rate was obtained for MY10 with ACH2 at pH 7, which corresponded to the double, as compared with non-modified AC. In a biological system using granular biomass, ACH2 also duplicated and increase 4.5-fold the decolourisation rates of MY10 and RR2, respectively. In this last experiment, reaction rate was independent of AC concentration in the tested range 0.1–0.6 g L−1.